THE PERCEPTION OF THE KIAI'S VIOLATED TOWARDS DIGITALIZATION OF ECONOMIC TRANSACTIONS - Ma'shum, AM. Muh. Khafidz (Jurnal Al-Iqtishad, 2023)
This paper aims to describe the Kiai's perception of violating the digitalization of economic transactions, which is limited to four areas, namely m-banking, e-money, e-wallet and financial technology. The research method used is qualitative using primary data sources from the field, where the research subjects are the offending Kiai who meet the criteria. Data was collected using interview and observation techniques. Data validity uses triangulation, member checking and emic methods. After coding, the data was analyzed using domain and taxonomy analysis techniques. The results that can be presented are the Kiai violating perceptions of the digitization of economic transactions divided into two, namely first the violating Kiai who are exposed to stimulus and direct experience of digitizing economic transactions at high intensity; and secondly, the Kiai violates with a low level of exposure and direct experience. Kiai violates the first category perceiving the digitization of economic transactions in the aspects of function and shariah compliance, in which the digitization of economic transactions is perceived as a transaction medium which is easy, practical, safe, efficient, comfortable, supports activities and does not conflict with sharia aspects. The Kiai violating the second category perceives the digitalization of economic transactions as merely a non-cash financial transaction. This research is expected to complement the theory of perception formation by adding a confirmation stage in the perception formation process. In addition, research also limits the applicability of the theory of agent of social change, meaning that kiai can act as agents of social change if they have the ability to adapt to the dynamics of civilization.